Sexual Dimorphism in Primate Aerobic Capacity: A Phylogenetic Test - Lindenfors, Patrik (2010)
Male intrasexual competition should favour increased male physical prowess. This should in turn result in greater aerobic capacity in males than in females (i.e., sexual dimorphism), and a correlation between sexual dimorphism in aerobic capacity and the strength of sexual selection among species. However, physiological scaling laws predict that aerobic capacity should be lower per unit body mass in larger than in smaller animals, potentially reducing or reversing the sex difference and its association with measures of sexual selection. We used measures of hematocrit and red blood cell (RBC) counts from 45 species of primates to test four predictions related to sexual selection and body mass: (i) on average, males should have higher aerobic capacity than females, (ii) aerobic capacity should be higher in adult than juvenile males, (iii) aerobic capacity should increase with increasing sexual selection, but also that (iv) measures of aerobic capacity should covary negatively with body mass. For the first two predictions we used a phylogenetic paired t-test developed for this study. We found support for predictions (i) and (ii). For prediction (iii), however, we found a negative correlation between the degree of sexual selection and aerobic capacity, which was opposite to our prediction. Prediction (iv) was generally supported. We also investigated whether substrate use, basal metabolic rate, and agility influenced physiological measures of oxygen transport, but we found only weak evidence for a correlation between RBC count and agility.